Интерпретация и использование измерений сенсора-дальномера в задачах управления автономным мобильным роботом - Сухоручкина, О.Н.; Прогонный, Н.В.; Воронов, М.А. (Управляющие системы и машины, 2017)
Рассмотрено практическое использование измерений дальномеров Sharp GP2Y0A02YK для анализа формы и положения объектов, находящихся в зоне функционирования мобильного робота при автономном выполнении им заданий. Предложен контекстно зависимый подход к сбору, интерпретации и использованию системой управления робота дальнометрических данных. Розглянуто практичне використання вимірів далекоміра Sharp GP2Y0A02YK для аналізу форми і положення об’єктів, розташованих у зоні функціонування мобільного робота під час автономного виконання ним завдань. Запропоновано контекстно залежний підхід до збору, інтерпретації і використання системою управління робота далекометричних даних. The problems of the practical use of measurements received from Sharp GP2Y0A02YK rangefinders for the analysis of the shape and position of the objects in the operation zone of the mobile robot while carrying out the autonomous tasks are considered. A context-dependent approach to the collection, interpretation and use of rangefinder data by robot control system is presented. The simple and inexpensive sources of data about the mobile robot (MR) environment, such as infrared or ultrasonic rangefinders are preferred for equipping domestic MR or other MR for nonprofessional users.The autonomous MR used in present research is equipped with Sharp GP2Y0A02YK analog infrared rangefinder. The statement of the problem for data collection and interpretation proposed in this article is related to the conditions of the autonomous indoor MR operation where the task of forming the models of surrounding objects can be replaced by the task of finding a plane contour of these objects. The specificity of the rangefinder data collection while carrying out such MR missions as: studying of the objects form and position, the adjustment of the environment model, the causes and types of the rangefinder data errors is indicated. The special features of the primary sets of rangefinder measurements and the corresponding points in the fixed coordinate system of the robot operation environment are considered. A preliminary segmentation of the original data for more effective filtering at continuous and monotonic subsets of points is proposed. Construction of the compact representation of objects contours is performed as a sequential linear approximation of the separate segments of the filtered rangefinder data. The illustrations of the sequential analysis results and interpretation of the original rangefinder data sets depending on the robot missions context are given.